Assessment of the current status of certified immunizing pharmacists in the Pharmacists in the Philippines - Calara, Nicole Kaye R.; Dagandan, Kerwin Kien A.; dela Peña, Amelyn O.; Peña, Imelda G. (Manila: Department of Pharmacy, College of Pharmacy, University of the Philippines Manila, 2023)
The Philippine Pharmacists Association (PPhA) launched the Immunizing Pharmacists Certification Program (|PCP) in April 2021, which allows Filipino pharmacists to provide immunization services. However, there is still a lack of documentation on the current status of certified immunizing pharmacists in the Philippines after completion of IPCP, and no feedback is given to the PPhA on whether the skills and competencies they obtained were sufficient to help them in practice. Therefore, this study aimed to assess the current status of certified immunizing pharmacists in the Philippines after the conferment of their certificates from the Immunizing Pharmacist Certification Program (IPCP). An interview was conducted with four pharmacists from different practice areas such as the hospital, academe, public health, and community. Furthermore, a survey questionnaire was disseminated to certified immunizing pharmacists, which contained questions on the competencies, challenges, and solutions employed. Out of the 525 certified immunizing pharmacists, only 40 answered the survey, leading to a non respondent rate of 92.4%. From the interview, the key informants believed that pharmacists under the different practice areas retained the expected competencies, although not all respondents from the academe and public health sector were able to pass the objective portion of the survey. Furthermore, almost half of the respondents were incorrect in the question under Competency 5. The challenges encountered were dependent on their individual experiences in the practice areas, although the common solution that was suggested was to create a society for immunizing pharmacists and provide continuous training for immunizing pharmacists.
Thesis (Bachelor of Science in Pharmacy)--University of the Philippines Manila, June 2023.
Keywords: Pharmacists. -- Immunization. -- Philippines; Immunization. -- Certificate -- Philippines